Molecularly Designed Nanoparticles by Dispersion of Self‐Assembled Organosiloxane‐Based Mesophases1. (6th June 2014) - Sakamoto, Shigeru; Tamura, Yasuhiro; Hata, Hideo; Sakamoto, Yasuhiro; Shimojima, Atsushi; Kuroda, Kazuyuki
Abstract The design of siloxane‐based nanoparticles is important for many applications. Here we show a novel approach to form core–shell silica nanoparticles of a few nanometers in size through the principle of "dispersion of ordered mesostructures into single nanocomponents". Self‐assembled siloxane–organic hybrids derived from amphiphilic alkyl‐oligosiloxanes were postsynthetically dispersed in organic solvent to yield uniform nanoparticles consisting of dense lipophilic shells and hydrophilic siloxane cores. In situ encapsulation of fluorescent dyes into the nanoparticles demonstrated their ability to function as nanocarriers.